Strategi Keberlanjutan Usaha Ekspor Peternakan Domba sebagai Komoditas Ekspor di Kabupaten Jember - Irham Fidaruzziar; Nanang Dwi Wahyono; Yossi Wibisono; Niswatin Hasanah (Jurnal Ilmiah Fillia Cendekia, 2022)
Lamb is an export commodity that has a role in increasing national income through excise and foreign exchange. Many factors can influence a farmer's decision to run a sheep farming business in the midst of very large demand. This study aims to analyze sustainability and design a sustainability strategy for the sheep export business in Jember Regency. The methodology used is Multi Dimensional Scaling (MDS) to analyze using 10 attributes. The results of the technology dimension analysis show that the sheep commodity export business in Jember is categorized as "quite sustainable" with a value of 60.88. The factor that greatly influences the technology dimension and needs to be considered is the suitability of existing technology with livestock needs, the attribute influence value is 4.47